Sources of economic renewal: from the traditional firm to the knowledge firm - Diego Rodriguez-Palenzuela (European Central Bank (ECB), 2001)
We build on the imperfection of intellectual property rights as the central motivation for the organization of firms. There are several characteristics specific to a theory of the firm grounded on the absence of intellectual property rights: monetary incentive schemes arise naturally as a element of the organization and strategy of the firm, since profits are verifiable; firm's boundaries and the degree of centralization respond to the same economic principle; the sunk cost of physical assets plays a role of 'anchoring' non-patentable knowledge inside the firm, improving the appropriability of intellectual capital. Moreover, the model implies that 'small' changes in primitives (particularly small reductions in entry costs) may have drastic implications in organizations, inducing firms to shift from a strategy of building up physical capital, which improves appropriability, to a strategy of reliance on employee 'empowerment' (under which employees combine equity holding with being fully informed). The former strategy is characterized instead by flat wages and by employees' restricted access to the intellectual capital of the firm. The model may shed light in the theoretical explanation of observed industrial restructuring.
Keywords: C70; D23; D43; D82; L11; L22; O31; 330